A clinical comparison simulation study using the Inventory of Problems-29 (IOP-29) with the Center for Epidemiologic Studies Depression Scale (CES-D) in Lithuania. Issue 2 (4th March 2022) - Ilgunaite, Guste; Giromini, Luciano; Bosi, Jessica; Viglione, Donald J.; Zennaro, Alessandro
Abstract: This article contributes to the growing research on the validity of the recently developed, Inventory of Problems – 29 (IOP-29) in the discrimination of feigned from bona fide mental or cognitive disorders. Specifically, we first developed a Lithuanian version of the IOP-29 and tested its validity on a sample of 50 depressed patients and 50 healthy volunteers instructed to feign depression. Next, we reviewed all previously published IOP-29 studies reporting on depression-related presentations ( k  = 5), and compared our results against previously reported findings. Statistical analyses showed that the Lithuanian IOP-29 discriminated almost perfectly between genuine and experimentally feigned major depression, with Area Under the Curve (AUC) = .98 ( SE = .01) and Cohen's d  = 3.31. When compared to previously published IOP-29 literature on this same topic, these findings may be characterized as similar or perhaps slightly more encouraging. Indeed, across all international, empirical studies considered in this article, Cohen's d ranged from 1.80 to 4.30, and AUC ranged from .89 to .99. Taken together, these findings contribute to supporting the strong validity and cross-cultural applicability of the IOP-29. They also provide additional support for its use in forensic evaluations.